A cross-sectional study of gender variations in dental anxiety among Pakistani undergraduate students - Syeda Lalarukh Saba Shah; Nazli Gul shujaat; Shujaat Hasan Idris; Hafsa Mahmood (Journal of University Medical & Dental College, 2024)
ABSTRACTBACKGROUND & OBJECTIVE:  This study investigates gender differences in dental anxiety among Pakistani undergraduate students to enhance their oral health awareness and help reduce the avoidance of necessary dental care. To study the gender variations in dental anxiety among Pakistani undergraduate students.METHODOLOGY: Data was collected from 350 students by using cross-sectional study design and the age of the students was 18-24 years. A non-probability convenience sampling technique was utilized. After getting institutional ethical permission, the study was carried out. Every participant provided their consent, and confidentiality was maintained. The significance level was set at 0.05, and a 95% confidence level was determined.RESULTS: 350 students responded to the survey. Dental anxiety was more prevalent in females than males and found to be associated with other risk factors like visits to the dentist (<0.001), fear of dental pain (0.021), dental treatment (0.030), fear of white coat (0.006) and concerns (0.002). The findings emphasized the need for stress-reduction techniques and exercises done by the doctor before starting the dental treatments. Furthermore, it is crucial to minimize, if not completely avoid, the causes of dental anxiety through effective counseling and communication.CONCLUSION: Dental fear is more common among female students, which is a barrier to receiving dental treatments. Therefore, decreasing dental anxiety could be accomplished by offering frequent dental education and public awareness regarding oral health.